The Relationship Between Defensive Pessimism, Goal Orientation, and Self-Esteem Among Nursing Students - Mohamed Hussein Ramadan Atta PhD, MSc, BSc, Rn; Esraa Elsayed Rushdan PhD, MSc, BSc, Rn; Nadia Waheed Elzohairy PhD, MSc, BSc, Rn (SAGE Publishing, 2024)
Introduction Academic achievement in nursing students is significantly influenced by their self-esteem and goal orientation. Defensive pessimism, a strategy where students set low expectations to prepare for potential failure, helps them stay motivated and focused. While this cognitive strategy can boost effort and performance, its relationship with self-esteem and goal orientation remains underexplored among nursing students, revealing a gap in understanding how these factors interact to influence academic success. Objective Assess the level and relationship between defensive pessimism, goal orientation, and self-esteem among nursing students at the Faculty of Nursing. Method Four hundred students were included in the research using a stratified sampling method followed by a simple randomization sampling technique to select 100 students from each academic year. Tools: The Defensive Pessimism Questionnaire, the Goal Orientation Scale, and the Self-Esteem Scale were used. Results 56.28% of participants had a low level of defensive pessimism, about two-thirds (62.30%) had a low level of goal orientation, and 70.0% of the students had a mild level of self-esteem. In addition, higher levels of defensive pessimism are significantly associated with stronger goal orientation ( r  = .291, p  < .001) but lower self-esteem ( r  = −.246, p  < .001). Additionally, self-esteem is significantly positively correlated with mastery-performance approach goals ( r  = .335, p  < .001; r  = .142, p  < .001) and significantly negatively correlated with mastery-performance avoidance goals ( r  = −.351, p  < .001; r  = −.041, p  < .001). Conclusion These findings highlight the complex interplay between defensive pessimism, goal orientation, and self-esteem in nursing students. Understanding these relationships is crucial for developing targeted interventions to enhance academic achievement and psychological well-being among nursing students, potentially by fostering adaptive goal-setting strategies and addressing the impacts of defensive pessimism on self-esteem.